2016
DOI: 10.5603/piap.2016.0018
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Pattern and Asthma in India

Abstract: Introduction: The study aimed to evaluate the association between food consumption pattern and asthma in Indian population. Material and methods: 125 asthma and corresponding age and sex matched healthy controls were recruited for the purpose of a study. A self-reported food-frequency questionnaire (NNR-Dietary Pattern in Asthma Questionnaire) comprising of 80 food and drink items, belonging to 15 groups, was developed based on routine dietary habits and ISAAC phase two and phase three questionnaires. Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Modern lifestyle factors and diet habits have also impacted asthma disease and frequency. While the wide fast food consumption, frequent soda intake, sedentary lifestyle and lack of physical activity and exercise have been associated with an increased asthma prevalence; milk, fruits and fish intake may have a protective association with asthma [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Modern lifestyle factors and diet habits have also impacted asthma disease and frequency. While the wide fast food consumption, frequent soda intake, sedentary lifestyle and lack of physical activity and exercise have been associated with an increased asthma prevalence; milk, fruits and fish intake may have a protective association with asthma [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Frequent intake of carbonated drinks and fast food was associated with a higher risk of childhood asthma in the present study and fast food was found to be an independent risk factor. Poongadan et al have reported a similar association of fast food with childhood asthma in Northern India [23]. The possible mechanisms suggested include increased levels of trans-fat, fatty acids, sodium, calorie content, and preservatives in fast foods.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies 13 , 15 , 18 , 29 , 30 conducted in different zones of India reported associations between various food items and allergic symptoms, but they were based on self-report without confirmation. Some food items, like cow’s milk and hen’s egg, were commonly reported allergens across all regions.…”
Section: Discussionmentioning
confidence: 97%